Universal access in human-computer interaction : designing novel interactions : 11th International Conference, UAHCI 2017, held as part of HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, Proceedings.: designing novel interactions : 11th International Conference, UAHCI 2017, held as part of HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, Proceedings. Part I (2017) - Unknown
No abstract available